Simulation of the resistance moment of single-piston compressor of ship refrigeration unit - Букарос, Андрей Юрьевич; Букарос, Валерия Николаевна; Онищенко, Олег Анатольевич (Technology audit and production reserves, 2015)
The article discusses the problem of mathematical modeling of the mechanical single-piston compressor of ship refrigeration unit. The dynamics of the crank mechanism is analyzed. Basic equations of the forces acting in the compressor are obtained on the basis of schematized indicator diagram and sequence of calculation of torque resistance is proposed. Simulation model is developed in the simulation environment Matlab/Simulink that enables the analysis of changes of resistance moment in the function of the rotation angle of the shaft of the drive motor, compressor design features and conditions of its operation. The verification of the model is conducted on example of the compressor ХКВ-6 of small refrigeration unit. Characteristic curve of resistance moment of resistance moment in the function of the rotation angle of the shaft of the drive motor during working the compressor RAC-6 in nominal mode on freon gas R-600a and air. With the described method of calculating and modeling it is revealed that the average value of the resistance moment of test compressor in both modes of operation corresponds to the marking and experimental data.